URGENSI PIDANA TUTUPAN: HARAPAN DAN TANTANGAN - Nadia Salsabila Hartin; Nathalina Nathalina (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2019)
The enactment of Law Number 20 of 1946 has added pidana tutupan in the list of criminal sanction in Article 10 a of Penal Code. This article provides new sanction to sentence the criminal who has done the actions driven by honorable purpose with pidana tutupan. It is historically written that pidana tutupan has been sentenced once by Military Supreme Court in Yogyakarta on 1948. This study uses normative legal research methods conducted to find solutions to existing legal problems. However, pidana tutupan has never been applied anymore in Indonesia, neither by general courts or the military courts. The absence of parameter to identify the honorable purpose has obscured its objectivity as a crime punishment. Nevertheless, the drafter of the New Penal Code argues that the existence of pidana tutupan is needed in Indonesian criminal law. The results of this study are trying to figure out the definition of honorable purpose in the Law Number 20 of 1946 about Tutupan Punishment and in the new draft of Indonesian Penal Code through analyzing court decision, historical records, and interview to related parties as to complement other data. In addition, this thesis also compared the concept of pidana tutupan with similar punishments in Germany and Japan.